Relative effects of LDL-C on ischemic stroke and coronary disease: A Mendelian randomization study. (12th March 2019) - Valdes-Marquez, Elsa; Parish, Sarah; Clarke, Robert; Stari, Traiani; Worrall, Bradford B.; Hopewell, Jemma C.
Abstract : Objective: To examine the causal relevance of lifelong differences in low-density lipoprotein cholesterol (LDL-C) for ischemic stroke (IS) relative to that for coronary heart disease (CHD) using a Mendelian randomization approach. Methods: We undertook a 2-sample Mendelian randomization, based on summary data, to estimate the causal relevance of LDL-C for risk of IS and CHD. Information from 62 independent genetic variants with genome-wide significant effects on LDL-C levels was used to estimate the causal effects of LDL-C for IS and IS subtypes (based on 12, 389 IS cases from METASTROKE) and for CHD (based on 60, 801 cases from CARDIoGRAMplusC4D). We then assessed the effects of LDL-C on IS and CHD for heterogeneity. Results: A 1 mmol/L higher genetically determined LDL-C was associated with a 50% higher risk of CHD (odds ratio [OR] 1.49, 95% confidence interval [CI] 1.32−1.68, p = 1.1 × 10 −8 ). By contrast, the causal effect of LDL-C was much weaker for IS (OR 1.12, 95% CI 0.96−1.30, p = 0.14; p for heterogeneity = 2.6 × 10 −3 ) and, in particular, for cardioembolic stroke (OR 1.06, 95% CI 0.84−1.33, p = 0.64; p for heterogeneity = 8.6 × 10 −3 ) when compared with that for CHD. Conclusions: In contrast with the consistent effects of LDL-C-lowering therapies on IS and CHD, genetic variants that confer lifelong LDL-C differences show a weaker effect on IS than on CHD. The relevance of etiologically distinct IS subtypes may contribute to the differences observed.